Sintilimab Combined With Albumin‐Bound Paclitaxel and SOX Regimen as Conversion Therapy for Unresectable Advanced Gastric Cancer Achieving Complete Remission: A Case Report and Literature Review - Yufan Tang; Boquan Zhou; Bingbing Wen; Ke Yu; Jiajia Jia; Ying Sha; Jixiang Liu; Luyao Li; Ruifang Fan (Clinical Case Reports, 2026)
ABSTRACT For carefully selected patients with unresectable advanced gastric cancer, immunochemotherapy combining PD‐1 inhibitor with albumin‐bound paclitaxel and S‐1/oxaliplatin may achieve deep remission and enable successful R0 resection. Our findings suggest that this multimodal conversion approach could be considered in selected cases with favorable performance status and MDT‐supported indications, as pathological complete remission appears to be attainable in this context.